O combate à corrupção globalizada e a proteção dos direitos humanos: perspectivas do transconstitucionalismo e diálogos entre as jurisdições local, regional e global - Monteiro Filho, Augusto César (2020)
The present work aims to undertake a critical study on corruption and its harmful consequences for the progressive implementation of human rights internally and internationally, with phenomenic reflexes and repercussions, in particular in the social and economic rights, especially those of a state-provided nature. It is the subject of corruption under study under the focus of prevention, detection and combat mechanisms, considered international and internal plans, including through mutual collaboration between nations, especially considering the circumstance of ignoring transnational illicit practices with deleterious effects beyond territorial lindes. Having said that, it will meet the problematization of the role of domestic law and international law in combining efforts aimed at curbing transnational corrupt practices, with a view to their ability to hinder the concretion of the objectives of our republic and, as well, those of the international community, in what is in the way with human rights – jus cogens. The prospects of transconstitutionalism in the species, as well as the necessary dialogical approximation between local, regional and global jurisdictions (cross jurisdictions) will be analyzed. The influence of the globalized environment and Brazil's greater insertion in the international economic scenario recommend the approach of international cooperation as a legal instrument for preventing and combating corruption, with a view to increasing interdependence of nations in the contemporary international order, coming, by corollary, the imperative of combining efforts to address complex and common themes, revealing the relevance of the phenomenon of corruption on the international political agenda. In this wake, the International Conventions that Brazil is a signatory to and its binding force will be visited, as well as the relevant role that the United Nations – UN has played in this mister